2006
DOI: 10.2337/dc05-1902
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose and Coronary Artery Disease in Nondiabetic Patients

Abstract: OBJECTIVE -Nondiabetic patients were studied to determine whether modest elevations in blood glucose may be associated with a greater incidence of coronary artery disease (CAD).RESEARCH DESIGN AND METHODS -Baseline morning blood glucose determinations were evaluated with respect to subsequent coronary disease using records from 24,160 nondiabetic patients. CAD was identified from myocardial infarction, new diagnoses of angina, or new prescriptions for nitroglycerin that occurred more than a year after baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…The biological importance of elevated FPG in simvastatin intervention and treatment rats identified in this study remains unknown, but data from the JUPITER trial [26] would suggest that the elevated FPG may translate into the clinical syndrome of diabetes with a rise in HbA1C. Besides, it has been demonstrated that there is a graded relationship between FPG and the levels of coronary artery disease severity [31]. The present estimates indicate that most individuals with prediabetic status may eventually develop clinical diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The biological importance of elevated FPG in simvastatin intervention and treatment rats identified in this study remains unknown, but data from the JUPITER trial [26] would suggest that the elevated FPG may translate into the clinical syndrome of diabetes with a rise in HbA1C. Besides, it has been demonstrated that there is a graded relationship between FPG and the levels of coronary artery disease severity [31]. The present estimates indicate that most individuals with prediabetic status may eventually develop clinical diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…High serum glucose is associated with earlier micro- and macro-vascular complications of DM. Furthermore, it has been demonstrated that fasting glucose may also be independently associated with the development and severity of atherosclerosis in non-diabetic patients (37, 38). Patients in all 3 groups of our study had similar DM rates, and fasting plasma glucose was positively correlated with Gensini score.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that there is a graded relationship between FPG and the extent of coronary artery disease severity. 13 Current estimates indicate that most individuals, up to 70%, with prediabetic status may eventually develop clinical diabetes mellitus. 14 Numerous longitudinal studies indicate that impaired FPG is associated with a modest increase in hazards ratio (1.1-1.4) for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%